PERKEMBANGAN MADRASAH DI INDONESIA - P Praptiningsih (MAMBA'UL 'ULUM, 2019)
Before madrasah or Islamic school is built, mosque functions generally for holding education and includes every activity. The development of Islamic school firstly comes in three stages: first, mosque, second, institution of Masjid-Khan and third is Madrasah or Islamic school. Madrasah in Indonesia is Islamic education institution having long history. The trace exploration of the Islamic school is started by efforts of developing Islamic education system conducted by either Islamic figures or social-religious organizations. The development is influenced by policies through time, Dutch colonialism period, Japan colonialism period, independence era, old-period, and new period in Indonesia. The regulation of Sisdiknas No.20 in 2003 it is explained “education channel consists of formal education, non formal education and informal education completed and enriched each other. The education stated in verse 1 is held using opened system through meeting and long distance.